Analisis Ketimpangan Ekonomi Dan Sektor Ekonomi Unggulan Di Kabupaten Muaro Jambi Provinsi Jambi - Agung Pambudi; Ida Nuraini; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2022)
The purpose of this study is to determine inequality and the leading economic sector in Muaro Jambi district with a period of 5 years from 2016 to 2020. The research method used is to use the Williamsom index calculation and Static Location Quotient by taking secondary data obtained from sources. Central Bureau of Statistics Muaro Jambi. The results of the study show that inequality is increasing from 2016 to 2020 from the calculation of the Williamson index. Meanwhile, from the calculation of the Static Location Quotient , the leading sectors in Muaro Jambi district are the agriculture, forestry and fishery sectors, processing industry, transportation and warehousing, and other services. The non-leading sectors in Muaro Jambi district are mining and quarrying, electricity and gas supply, water supply, waste management, waste and recycling, construction, wholesale and retail trade, car and motorcycle repair, accommodation and food and drink provision, information and communication, financial and insurance services, real estate, corporate services, government administration, defense and compulsory social security, education services, and health services and social activities.